Role of P450 1A1 and P450 1A2 in bioactivation versus detoxication of the renal carcinogen aristolochic acid I: studies in Cyp1a1(−/−), Cyp1a2(−/−), and Cyp1a1/1a2(−/−) mice - Arlt, Volker M.; Levová, Kateřina; Bárta, František; Shi, Zhanquan; Evans, James D.; Frei, Eva; Schmeiser, Heinz H.; Nebert, Daniel W.; Phillips, David H.; Stiborová, Marie (Chemical research in toxicology, 2011)
Exposure to aristolochic acid I (AAI) is associated with aristolochic acid nephropathy, Balkan endemic nephropathy, and urothelial cancer. Individual differences in xenobiotic-metabolizing enzyme activities are likely to be a reason for interindividual susceptibility to AA-induced disease. We evaluated the reductive activation and oxidative detoxication of AAI by cytochrome P450 (P450) 1A1 and 1A2 using the Cyp1a1(−/−) and Cyp1a2(−/−) single-knockout and Cyp1a1/1a2(−/−) double-knockout mouse lines. Incubations with hepatic microsomes were also carried out in vitro. P450 1A1 and 1A2 were found to (i) activate AAI to form DNA adducts and (ii) detoxicate it to 8-hydroxyaristolochic acid I (AAIa). AAI-DNA adduct formation was significantly higher in all tissues of Cyp1a1/1a2(−/−) than Cyp1a(+/+) wild-type (WT) mice. AAI-DNA adduct levels were elevated only in selected tissues from Cyp1a1(−/−) versus Cyp1a2(−/−) mice, compared with those in WT mice. In hepatic microsomes, those from WT as well as Cyp1a1(−/−) and Cyp1a2(−/−) mice were able to detoxicate AAI to AAIa, whereas Cyp1a1/1a2(−/−) microsomes were less effective in catalyzing this reaction, confirming that both mouse P450 1A1 and 1A2 are both involved in AAI detoxication. Under hypoxic conditions, mouse P450 1A1 and 1A2 were capable of reducing AAI to form DNA adducts in hepatic microsomes; the major roles of P450 1A1 and 1A2 in AAI-DNA adduct formation were further confirmed using selective inhibitors. Our results suggest that, in addition to P450 1A1 and 1A2 expression levels in liver, in vivo oxygen concentration in specific tissues might affect the balance between AAI nitroreduction and demethylation, which in turn would influence tissue-specific toxicity or carcinogenicity.